Deontic Paradoxes and Tableau System for Kalinowski’s Deontic Logic K1 - Ciuciura, Janusz (Bulletin of the Section of Logic, 2017)
In 1953, Jerzy Kalinowski published his paper on the logic of normative sentences. The paper is recognized as one of the first publications on the formal system of deontic logic. The aim of this paper is to present a tableau system for Kalinowski’s deontic logic and to discuss some of the topics related to the paradoxes of deontic logic.